Food Security Achievement through Women Empowerment: A Study of Informal Sector in Lahore - Haifa Asif; Shahzad Ali (Journal of Nutrition and Food Security)
Women empowerment (WE) in food security is one of the global issues faced by women in all the countries of the world. Achievement of zero-hunger goal of Sustainable Development Goals in 2030 (SDG) still seems to be unachievable because of this food insecurity. This research aims to study the achievement of food security by enhancing WE in the informal sector in Lahore, Pakistan. Moreover, the analysis goals are to determine the contribution of microcredit facilities and management skills in the enhancement of WE which improves food security. Method: This study was quantitative and descriptive. Using a primary survey questionnaire on cross-sectional data source by simple random sampling, 495 women borrowers in the informal sector of Lahore, Pakistan were investigated. Data analysis was done using SMART PLS3. Results: The results of the study revealed a positive relationship between WE and food security through the active participation of women in production decisions. The utilization of resources within the households is strengthened by familial rights, social support, and the removal of gender disparity. Conclusion: Women's capacity to contribute more to the daily household expenditure is increased by the higher income, and eventually, it increases their empowerment and food security.